Contract Amendment in the State Procurement Law (Law No. 30225) - Zegarra Pinto, José (2015)
The present article has as principal goal to analyze and comment the more relevant aspects referred to the amendments on that can be done to a contract, in the terms allowed by the new Public Procurement Peruvian Law. Also, the author will refer to the opinions emitted by the OSCE about the topic. Finally, he will state his main conclusions.